Using M-Learning Technology in Teaching Foreign Languages: A Panacea during COVID-19 Pandemic Era - Dolzhich, Elena; Dmitrichenkova, Svetlana; Ibrahim, Mona Kamal (International Journal of Interactive Mobile Technologies (iJIM), 2021)
The higher education system around the world is being rapidly developed towards digitalization – from computers to laptops, from laptops to tablets and smartphones. Accordingly, traditional delivery of instruction is being shifted towards blended learning that is being gradually replaced with distance learning, i.e. higher education is moving forward with mobile learning (m-learning) technologies. The introduction of mobile learning became the most topical event in 2020 in the context of the COVID-19 pandemic, due to which many countries had to completely move to distance learning in higher education. The purpose of the study is to analyze the prospects for the widespread use of mobile applications in teaching English as a foreign language (EFL) in Russia to Russian and Arab learners. In the course of the study, an online survey based on a questionnaire consisting of four open and closed questions was conducted. An empirical method was applied to collect the research data. The survey was conducted at the Department of Foreign Languages of the Engineering Academy of the Peoples’ Friendship University of Russia (EA PFUR). The total research sample included 200 participants and consisted of: 50 potential employers, 50 Russian and Arab students of the Peoples’ Friendship University of Russia studying Linguistics (training program code 035700), 50 faculty members, namely teachers of the Peoples’ Friendship University of Russia, the Institute of Foreign Languages of the Moscow State Pedagogical University and the Moscow Institute of Physics and Technology, as well as 50 administrative staff of the Peoples’ Friendship University of Russia. The purpose of the survey was to collect information about the use of mobile applications (Smartphone Apps) and the introduction of mobile learning technology (m-learning) in the process of teaching EFL to students. According to the results of the survey, instructors are actively using mobile technologies in their professional activities and all participants in the learning process are receptive to their introduction in education. At the same time, respondents believe that technical challenges are the major obstacle to the adoption of mobile applications; these problems must be overcome in order to enable more productive use of mobile applications. In this regard, the study of mobile applications that are suitable for specific aspects of learning a foreign language, such as spoken language, reading comprehension, listening or writing, can be considered a promising research area.